2004
DOI: 10.1074/jbc.m410395200
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Ovarian Cancer Cell Apoptosis by 1,25-Dihydroxyvitamin D3 through the Down-regulation of Telomerase

Abstract: The maintenance of telomere length is required for continued cell proliferation, and ϳ85-90% of human cancers, including ovarian epithelial cancers (OCa), show high activity of telomerase. In the present study we report that 1,25-dihydroxyvitamin D 3 (1,25(OH) 2 Vitamin D is a lipophilic hormone, and its effects are mediated by the vitamin D receptor (VDR) 1 (1), which is a member of the steroid/thyroid nuclear receptor superfamily. This superfamily includes receptors for steroids such as progesterone, androg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
108
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(114 citation statements)
references
References 31 publications
3
108
0
3
Order By: Relevance
“…39,40 In addition, vitamin D inhibits the expression of telomerase, an enzyme that adds a specific DNA sequence repeat to the 3 0 end of DNA strands, resulting in cell death. 41,42 In the current investigation, we noted that supplementation with 22-oxa-D 3 also up-regulated the expression of VDR, a receptor that is necessary for the genomic action of vitamin D. This observation is was evident in cell cultures, in the mouse model, and in the HDRA. It also has been demonstrated that the antitumor growth …”
Section: Discussionmentioning
confidence: 50%
“…39,40 In addition, vitamin D inhibits the expression of telomerase, an enzyme that adds a specific DNA sequence repeat to the 3 0 end of DNA strands, resulting in cell death. 41,42 In the current investigation, we noted that supplementation with 22-oxa-D 3 also up-regulated the expression of VDR, a receptor that is necessary for the genomic action of vitamin D. This observation is was evident in cell cultures, in the mouse model, and in the HDRA. It also has been demonstrated that the antitumor growth …”
Section: Discussionmentioning
confidence: 50%
“…After ligand binding, the VDR forms a heterodimer with retinoid X receptor (RXR) and binds to vitamin D-responsive elements (VDREs) in the regulatory region of target genes to activate or repress their transcription (23). Previous studies have shown that the growth of multiple human ovarian cancers was suppressed by 1,25(OH) 2 D 3 (24,25) and that 1,25(OH) 2 D 3 -induced apoptosis involved down-regulation of telomerase activity (26). This study identifies miR-498 as a primary target gene for 1,25(OH) 2 D 3 , which binds to the 3Ј-UTR of hTERT and decreases its mRNA expression to induce cell death.…”
mentioning
confidence: 77%
“…cDNA was reverse-transcribed from 1 g of total cellular RNA with random hexamer primers and thermostable reverse transcriptase (Invitrogen). Analyses of hTERT and GAPDH expression by RT-PCR were performed as described previously (26). To quantify hTERT and GAPDH expression, PCR products were subjected to electrophoresis in a 15% polyacrylamide gel.…”
Section: Materials Cell Lines and Human Tissues-125(oh)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has also reported that some breast cancer cells shows potentiate TNF alpha induced apoptosis through the death receptor pathway, which is linked to the activation of caspases and phospholipase A2 (Colston and Hansen, 2002). A novel mechanism of 1α 25(OH) 2 D 3 -mediated apoptosis in epithelial ovarian cancer cells was proposed by Jiang et al(2004), wherein they showed that 1 α 25(OH) 2 D 3 destabilizes telomerase reverse transcriptase (TERT) mRNA, therefore inducing apoptosis through telomere attrition resulting from the down-regulation of telomerase activity and it is first study which demonstrate stability of hTERT mRNA by a hormone. The proposed mechanism for induction of apoptosis followed by the 1α 25(OH) 2 D 3 -VDR complex induces Vitamin D3-Upregulated Protein 1 and 2, which negatively regulates thioredoxin function and expression.…”
Section: Cyp24a1mentioning
confidence: 99%